Construction of moral values education course module for pre-services teachers - Akhmetova, Elmira; Ariffin, Adlina; Souad, Merah; Faris, Waleed Fekry; Quayum, Mohammad Abdul; Tahraoui, Ramdane (IIUM Press, 2021)
This monograph is a Final Report of the project C-RIG18-005-0005 entitled CONSTRUCTION OF MORAL VALUES EDUCATION COURSE MODULE FOR PRE-SERVICE TEACHERS. This collaborative research between IIUM, Istanbul Foundation for Science and Culture from Turkey, Pereyaslav Pedagogical State University from Ukraine, and Shura Trust from the UK, aimed to search for ways to bring a soul to modern education by the construction of course module embedded with moral values and holistic approach for pre-service teachers.